A study of Diagnosis and surgical management of pancreatic insulinoma - Chinthakindi, Madhusudhan; Prashanth, Kyyoda; Thogari, Ravimohan; Pratap Reddy, Ramalingam (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2018)
Introduction: Insulinomas are the most common functioning neuroendocrine tumors of the pancreas, occurring in almost 1-4 per 1 million persons each year. They pose a challenge for pre-operative localization. Many invasive and non-invasive methods exist for localization of an insulinoma. Intra-operative ultrasonography (IOUS) with palpation can be done for tumors not localized by conventional imaging modalities. Pancreas Preserving surgery is the treatment of choice. This article gives an overview on localization and surgical strategies for treatment of insulinoma. Materials and Methods: This is a retrospective data of the patients undergoing surgical treatment of insulinoma in the Osmania General Hospital, Hyderabad between 2007 to 2017. Demographic data, symptoms and diagnostic tests and type of resections were analyzed from medical records. All patients had a complete intraoperative exploration of the pancreas done by digital palpation and intra operative ultrasonography. Results: 10 cases (6 males and 4 females) of insulinoma aged between 22 and 55 years, with a median age of 30 years were included in the analysis. The size of the insulinoma ranged between 1.2 to 3 cm with average size of 2.14cm. 8 patients presented with Neuro glycopenicsymptoms however sympatho adrenergic symptoms were present in all cases. Different modalities were employed for pre-operative localization of these patients out of which 5 cases were localized with CT, 2 cases with MRI, 1 case with EUS, 2 of them could not be localized preoperatively were localized by IOUS. Tumor was in Head 2 cases, in the neck1 case and in the body/ Tail in 7 cases. 2 patients underwent Enucleation, 5 underwent distal pancreatectomy and splenectomy, 2 under went distal pancreatectomy and 1 underwent central pancreatectomy. 4 had pancreatic leak. All are symptom free and no episode of hypoglycemia at the time of discharge. Conclusion: Insulinomas are the most common neuroendocrine tumors of the pancreas. Surgical resection is the treatment of choice for insulinomas. From a surgical stand point, localization of the tumor is of critical importance. Intraoperative Ultrasonography with palpation gives good help in localizing the lesion.